AUTOMOBILE CRASH BOX IMPROVEMENT AND FORMING ANALYSIS FOR TUBE HYDROFORMING - XU MingTao; WANG LiJuan; CHEN ZongYu; CHENG JiangHong (Jixie qiangdu)
The automobile crash box is an important buffering and absorbing energy structure.Due to the advantages of light weight,high stiffness,high strength and good crashworthiness for hydroforming tubular,the hydroforming crash box is designed instead of the stamping and welding structure.By numerical simulation,analysis the crash box key energy absorption properties,comparison of tube hydroforming crash box and stamping one absorbing performance.Design the load-curves for Tube Hydroforming automobile crash box,which is influence the crash box thickness distribution after forming.In this paper,maximizing of the minimum wall thickness of crash box after hydroforming is used as the research object,select the pressure control parameter on the load-curves as design variables,using fractional factorial designed experiment,then use of Kriging spatial interpolation method to build approximation model,Finally,the use of genetic algorithm to obtain the optimized loadcurves,increasing the minimum wall thickness of crash box after hydroforming.